(untitled) (GYMNASIUM, 2017)
The purpose of this comparative study is to calculate the gender relations of proportionality between anthropometric measurements in the frontal plane and height respectively to monitor the growth and development of small pupil. For a better organization of research, we started from the hypothesis: suppose a study by ascertaining the gender relations of proportionality between anthropometric measurements in the frontal plane and height, it can determine whether children have normal growth and the harmonious physical development, compared to the two sexes. Research methods used were determined according to the research objectives, such bibliographic study method was used, the method of measurement and evaluation, statistical and mathematical method and graphical method. Following this study, it appears that the statistical analyzes performed proportional relations in the frontal plane and height, children have normal growth and harmonious physical development in both sexes compared with small differences between the values.